Overcoming severe adverse reactions to venom immunotherapy using anti‐IgE antibodies in combination with a high maintenance dose. Issue 12 (28th September 2017) - Stretz, E.; Oppel, E. M.; Räwer, H.‐C.; Chatelain, R.; Mastnik, S.; Przybilla, B.; Ruëff, F.
Summary: Background: An omalizumab treatment and a high maintenance venom dose may both help to prevent recurrent systemic allergic reactions (SAR) to venom immunotherapy (VIT). The effectiveness of this combination therapy, however, is unclear. Objective: We wanted to explore the possibility whether a temporary treatment with the anti‐IgE antibody omalizumab combined with a VIT using an elevated maintenance dose of >100 μg venom may establish a permanent tolerance of maintenance VIT. Methods: For this retrospective case series, we scoured our institutional data base for patients who had had an insect venom allergy, and in whom it had not been possible to continue VIT because of repeated unstoppable SAR during maintenance VIT. Patients were divided into those who had received the combination therapy (omalizumab group) and those who had not received omalizumab because its costs could not be covered (controls). Guided by the total IgE level and by body weight, omalizumab had been given subcutaneously 5, 3 and 1 weeks before VIT had been restarted. Three to 6 months after an elevated maintenance dose (200‐300 μg venom) had been reached, omalizumab had been stopped. Results: Between 2006 and 2011, 15 patients had qualified for an off‐label use of omalizumab: 10 patients had received the combination therapy, and 5 patients had remained without such a therapy. The combination therapy leads to a durable tolerance of VIT in all patients even after omalizumab had been discontinued (median of follow‐up time 5.8 years, IQR 2.7‐8.6 years). Sting challenge tests were tolerated by all of the re‐stung omalizumab patients (n = 8). In all controls, VIT had to be stopped permanently due to repeated SARs ( P < .001 vs omalizumab group). Conclusions and Clinical Relevance: Combining a temporary omalizumab therapy with an elevated maintenance dose seems a promising approach to achieve a tolerance of treatment in patients with a recurrent SAR to VIT.